KOMPETENSI GURU, SPIRITUAL INTELLIGENCE, SELF DETERMINATION THEORYDAN ORGANIZATION CITIZENSHIP BEHAVIOR - Jayadi Jayadi (Universitas Ahmad Dahlan, 2012)
AbstractThe purpose of this study was to examine the factors that affect the organization citizenship behavior, namely teacher competence, spiritual intelligence, and self-determination theory in junior high school teacher. Some 231 junior high school teachers in East Kotawaringin Sampit are given four scales to fill in, namely teacher competence scale, spiritual intelligence scale, self-determination theory scale and organization citizenshipbehavior scale. Data was analyzed with statistical techniques namely structural equation model (SEM). The results showed there is the influence of teacher competence in self-determination theory (ë= 0.147, p = 0.003).The influence of spiritual intelligence to self-determination theory was significant ( = 0874, p = 0.000). There is a significant influence of teachers’ competencies on organizational citizenship behavior (ë = 0097, p = 0.007). There is no significant influence of spiritual intelligence to organizational citizenship behavior (ë= 0070, p = 0461), but the effect through selfdetermination theory (ë= 0808). There is a significant influence of selfdetermination theory to organizational citizenship behavior (ë= 0924, p =0.000).Keywords: organizational citizenship behavior, self determination theory, spiritual intelligence, teacher competency